The path of thorns - Slatter, Angela (Titan Books, 2022)
A lush and twisted dark fairy tale suffused with witchcraft, dark secrets and bitter revenge from the award-winning author. Exquisite, haunting and at times brutal, readers of Naomi Novik and Erin Morgenstern will be entranced. Asher Todd comes to live with the mysterious Morwood family as a governess to their children. Asher knows little about being a governess but she is skilled in botany and herbcraft, and perhaps more than that. And she has secrets of her own, dark and terrible -- and Morwood is a house that eats secrets. With a monstrous revenge in mind, Asher plans to make it choke. However, she becomes fond of her charges, of the people of the Tarn, and she begins to wonder if she will be able to execute her plan -- and who will suffer most if she does. But as the ghosts of her past become harder to control, Asher realizes she has no choice. From the award-winning author of All the Murmuring Bones, dark magic, retribution and twisted family secrets combine to weave a bewitching and addictive tale.